Analysis of Consumers Participation in Packaging Waste Management in Yogyakarta City: Analisis Partisipasi Konsumen dalam Pengelolaan Sampah Kemasan Di Kota Yogyakarta - Intan Har Aselna; Mochammad Chaerul (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
E-commerce activities have shown significant growth, especially during the Coronavirus Disease (Covid-19) pandemic, driving an increase in packaging waste generated by consumers from their online purchases. Similar to other cities, Yogyakarta City has waste management facilities at source, but the existence of this infrastructure has not significant reduced the amount of waste transported to the Piyungan landfill. This study aimed to predict consumer behavior and measure their willingness to participate in packaging waste management through the Theory of Planned Behaviour (TPB) model. Data was collected through structured questionnaires distributed to 111 respondents in 14 subdistricts in Yogyakarta city which were then analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM). The results showed that knowledge, perceived behavioral control, and convenience had a significant effect, while subjective norms and attitudes had a insignificant effect on the willingness of consumers participation in packaging waste management.